LandESCAPE creating an outdoor escape room for artwork promotions in Bonifacio High Street - Taguibulos, Marcus Jonas Isaias T.
The popularity of escape rooms has grown for many years. There have been various studies that have used escape rooms as a medium for purposes such as education and tourism. If it could be used for purposes mentioned, then making an outdoor version would prove new ways for us to use this. Currently, the use of Escape Rooms is limited to indoor uses. With escape rooms not fully explored, the plausibility of outdoor versions of escape rooms was realized. The researcher collected data through review of literature, surveys, site visits and consultations from experienced people. From these methods, the collected data are used as parameters and guidelines in designing an outdoor escape room. Using escape rooms for the landscape. An integration of escape rooms to the open space will be a necessary approach. Though it has been established that a good number of users have already used or are interested in using escape rooms, there will still be a good number of people that will not be interested in spending these kinds for various reasons. That very fact must be taken into consideration as these will be within open spaces.